Social and cultural geography - Ocal, Tulay; Altuner, Huriye; Killian, S.; Penfield, Megan; Ferilli, Guido; Sacco, Pier Luigi; Buscema, Massimo; Blessi, Giorgio Tavano (Magnum Publishing, 2016)
"Social geography is closely related to social theory in general and sociology in particular, dealing with the relation of social phenomena and its spatial components. In cultural geography, we study about cultural products and norms and their disparities and relations to spaces and places. It focuses on describing and analyzing the ways language, religion, economy, government and other cultural phenomena differ or persist constant, from one place to another and on explaining how humans function spatially. Social and Cultural Geography emphasizes on the topics with the patialities of society and culture, particularly the role of space, place and culture in relation to social issues, cultural politics, aspects of daily life, cultural commodities, consumption, identity and community, and historical legacies."--Back cover.